ПСИХОЛОГО-ПЕДАГОГІЧНІ ПРОБЛЕМИ ФОРМУВАННЯ МОТИВАЦІЇ УЧБОВОЇ ДІЯЛЬНОСТІ - Луценко, Олена (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті порушені питання вирішення основних психолого-педагогічних проблем формування учбової мотивації курсантів вищих навчальних закладів МВС України. Розглянуті перспективні шляхи застосування в практиці правоохоронної освіти методів і засобів учбової діяльності курсантів за допомогою новітніх дидактичних форм і методів. аведено аналіз сучасної практики застосування інноваційних форм професійної освіти у вищих навчальних закладах МВС України. Розкрито соціальну значимість мотивованого навчання в системі професійної освіти у вищих навчальних закладах системи МВС України. В статье затронуты вопросы решения основных психолого-педагогических проблем формирования учебной мотивации курсантов высших учебных заведений МВД Украины. Рассмотрены перспективные пути применения в практике правоохранительного образования методов и средств учебной деятельности курсантов с помощью новейших дидактических форм и методов. Приведен анализ современной практики применения инновационных форм профессионального образования в высших учебных заведениях МВД Украины. Раскрыто социальную значимость мотивированного обучения в системе профессионального образования в высших учебных заведениях системы МВД Украины. The article raised such questions as how to solve the major psychological and pedagogical problems of formation of educational motivation of students of higher educational establishments of Ukraine. Perspective ways used in the practice of law enforcement education methods and means of learning of students with the latest teaching forms and methods are considered. An analysis of the current practice of innovative forms of vocational education in higher educational establishments of Ukraine is shown. Special procedures of motivation activation of cadets’ achievements such as training courses were developed. The article explores the educational motivation and cognitive interest which were distinguished together with social motives as the main motivating factors to training. Hierarchical and structural relations between the cognitive interest and other motives, the mechanisms of functioning of educational motivation, the content and dynamic characteristics of motives were considered. As the training process in higher educational establishments of the MIA of Ukraine has its peculiarities so the motivational sphere of cadets require the special approaches to motive formation of their educational activities. The influence of external and internal motives on the behavior and psychological processes was examined in the article. In addition, the balanced structure of cadets’ educational motives was formed. To build the professional orientation and motivation of future police on the stage of primary education is an important component of improving the quality of vocational education.